Working Within a Public Health Frame: Toward Health Equity Through Cultural Safety - McAlister, Seraphina (Université d'Ottawa / University of Ottawa, 2013)
This study explored how public health nurses (PHNs) work to address health inequities. Cultural safety was used as a theoretical lens. Methods for interpretive description were relied on for data collection and analysis. Data sources included interviews with 14 staff from an urban public health unit and document review of three policies. Two themes emerged: building relationships and working within a frame. Building relationships involved: delivering the message, taking the time, being present, the right nurse and learning from communities. The public health frame influenced the capacity of PHNs to address health inequities through: culture and stereotypes, public health standards, setting priorities, inclusion of priority populations, responding to change and (re)action through reorganization. Discursive formations of priority populations, and partnership and collaboration, were revealed. Findings highlighted downstream public health approaches to addressing health inequities. Importantly, embedding cultural safety as a framework for public health practice can guide upstream action.
Keywords: Public health nursing; Cultural safety; Health inequity